Interactions between Copper(II) complexes of mono-, bis-, and tris(macrocyclic) ligands and inorganic or organic guests - Comba, Peter (European journal of inorganic chemistry, 2002)
The copper(II)-assisted condensation of [Cu(2,3,2-tet)]2+ [2,3,2-tet = bis-N,N′-(2-aminoethyl)propane-1,3-diamine] with formaldehyde and melamine (melamine = 2,4,6-triamino-1,3,5-triazine) afforded melamine-based mono-, bis-, and tris(macrocyclic) ligand/copper(II) complexes in approx. 30% overall yield. Three different monocopper(II), one dicopper(II), and one tricopper(II) complex structures are reported, as well as two structures of host-guest assemblies of the tricopper(II) complex with benzene-1,3,5-tricarboxylate and one resulting from a reaction with hexacyanoferrate(II) to afford an octanuclear Cu6Fe2 complex. These structures are discussed together with those of five previously reported similar compounds, and it is concluded that the two conformations of the tricopper(II) complex are similar in energy and that they are easily interconverted. The range of the structural flexibility of the tricopper(II) host is analyzed on the basis of the experimental structural data. The formation of the Cu6Fe2 assembly is assumed to be a stepwise procedure, the formation of the structurally previously unknown [Fe2(CN)11]7− anion is assisted by the Cu3 host cation, and the host-guest assembly is stable in solution.